2020
DOI: 10.4103/jpn.jpn_143_16
|View full text |Cite
|
Sign up to set email alerts
|

Giant anterior fontanel encephalocoele: A rare case report and review of literature

Abstract: A BSTRACT An encephalocoele is a spectrum of cranial dysraphism caused due to defective closure of neural tube during early embryonic life, leading to formation of a cerebrospinal fluid (CSF)–filled sac containing brain tissue and meninges, all herniated through a bony defect of the skull. Anterior encephalocoeles, though rare in the Western world, are relatively common in southeast Asia, including some parts of India. Among anterior encephalocoeles, fronto-ethmoidal type is the most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Sialylated compounds inhibit the adhesion of toxins, bacteria and viruses to epithelial cell surface receptors and promote the growth of Bifidobacterium and Lactobacillus. [18][19][20] NEC is one of the most common and fatal intestinal diseases in premature infants, and treatment options are very limited. The NEC risk of breastfed infants is 6-10 times lower than that of formula-fed infants, and we have previously shown that HMOs improve survival and reduce pathology in rat NEC models.…”
Section: The Structures and Compositions Of Hmosmentioning
confidence: 99%
“…Sialylated compounds inhibit the adhesion of toxins, bacteria and viruses to epithelial cell surface receptors and promote the growth of Bifidobacterium and Lactobacillus. [18][19][20] NEC is one of the most common and fatal intestinal diseases in premature infants, and treatment options are very limited. The NEC risk of breastfed infants is 6-10 times lower than that of formula-fed infants, and we have previously shown that HMOs improve survival and reduce pathology in rat NEC models.…”
Section: The Structures and Compositions Of Hmosmentioning
confidence: 99%